2021
DOI: 10.1038/s41564-020-00832-5
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Rho GTPase-activating toxin CNF1 mediates NLRP3 inflammasome activation via p21-activated kinases-1/2 during bacteraemia in mice

Abstract: Summary Inflammasomes are signaling platforms that are assembled in response to infection or sterile inflammation by cytosolic pattern recognition receptors (PRRs). The consequent inflammasome-triggered Caspase-1 activation is critical for the host defense against pathogens. During infection, NLRP3, a PRR also called Cryopyrin, triggers the assembly of an inflammasome activating Caspase-1 via the recruitment of ASC and Nek7. The NLRP3 inflammasome activation is tightly control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 55 publications
(74 reference statements)
2
48
0
2
Order By: Relevance
“…Interestingly, even if rectal temperature was different before infection ( Fig 1A ), the fever measured 4 hours after bacterial infection was equivalent between NaCl- and CL316,243-treated mice. As expected, the bacteremia was decreased at 24 hours and completely resolved after 48 hours, demonstrating bacteria clearance by mice ( Fig 3B ) [ 22 ]. Activation of brown and brite adipocytes did not modify this response to infection ( Fig 3B ).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…Interestingly, even if rectal temperature was different before infection ( Fig 1A ), the fever measured 4 hours after bacterial infection was equivalent between NaCl- and CL316,243-treated mice. As expected, the bacteremia was decreased at 24 hours and completely resolved after 48 hours, demonstrating bacteria clearance by mice ( Fig 3B ) [ 22 ]. Activation of brown and brite adipocytes did not modify this response to infection ( Fig 3B ).…”
Section: Resultssupporting
confidence: 72%
“…At the end of this treatment, half of the mice of each group were infected with E . coli and monitored 48 hours as previously described [ 22 ]. While bacteria induced a decrease of body weight in NaCl treated mice, no additive effect was found in CL316,243 treated mice ( Fig 1B ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In agreement with the in vivo results, our in vitro data showed that the expression of NEK7 in both types of macrophages was decreased during S. aureus infection, simultaneously, the formation of NEK7 and NLRP3 complexes was increased ( Figures 2A–C ). Consistently, some studies reported that the expression of NEK7 was decreased with the enhanced interaction of NEK7-NLRP3 under the stimulation of LPS and ATP ( 25 ), LPS and cytotoxic necrosis factor (CNF1) ( 26 ) or LPS and IgA ICs ( 27 ). Furthermore, S. aureus infection-induced expression of NLRP3 inflammasome-associated molecules were significantly decreased by NEK7-siRNA pretreatment ( Figures 2D–F ), suggesting that NEK7 participated in NLRP3 inflammasome activation.…”
Section: Discussionmentioning
confidence: 54%
“…Thus, Rac1 influences the mechanical response/adaptation of cells via the aforementioned functions. It is now important to define how to position Rac-mediated control of cell functions in the context of mechanosensing, given that ECM stiffening and abnormal responses to mechanical cues of the ECM are associated with a large spectrum of human diseases, including cancer and chronic inflammation [41][42][43][44][45] , and that Rac1 plays a critical role in the control of cell-extracellular matrix (ECM) adhesion, transcriptional responses, and cell division [46][47][48] and is frequently highjacked by invasive pathogens during infectious processes [49][50][51][52][53] .…”
Section: Introductionmentioning
confidence: 99%